When basal insulin is not enough: A dose–response relationship between insulin glargine 100 units/mL and glycaemic control. Issue 6 (25th March 2019) - Umpierrez, Guillermo E.; Skolnik, Neil; Dex, Terry; Traylor, Louise; Chao, Jason; Shaefer, Charles
Abstract : Aims: A post‐hoc analysis to assess the impact in people with type 2 diabetes, of increasing doses of basal insulin on glycaemic measures, body weight and hypoglycaemia. Research Design and Methods: We included data from prospective, randomized controlled treat‐to‐target trials of ≥24 weeks' duration in people with type 2 diabetes, uncontrolled on metformin and sulphonylureas, and treated with insulin glargine 100 units/mL (U100), who had at least six fasting plasma glucose (FPG) measurements. The impact of insulin dose on glycated haemoglobin (HbA1c) values, FPG, hypoglycaemia incidence (<3.9 mmol/L [70 mg/dL]), and body weight was analysed. A total of 458 participants from three eligible trials were included. Results: The observed relationship between higher basal insulin doses and glycaemic control was non‐linear, with increasing insulin dose leading to smaller reductions in FPG and HbA1c for doses >0.3 IU/kg/d, with a plateauing effect at 0.5 IU/kg/d. Total daily dose of insulin >0.5 IU/kg/d resulted in greater weight gain, but without higher rates of hypoglycaemia, compared with insulin doses ≤0.5 IU/kg/d. Conclusions: This analysis indicates that basal insulin doses >0.5 IU/kg/d have diminishing additional impact on improving glycaemic measures, with the disadvantage of additional weight gain. Clinicians should consider anti‐hyperglycaemic treatment intensification at doses approaching 0.5 IU/kg/d.